MO600: Effects of Intradialytic Progressive Resistance and Aerobic Exercise Training on Physical Function. (3rd May 2022) - Cardoso, Daniela; Vaz Leal, Diogo; Martins, Pedro; Anibal A Ferreira, Manuel; Baker, Luke; Smith, Alice; Viana, João
Abstract: BACKGROUND AND AIMS: Haemodialysis (HD) patients frequently experience reduced physical function, which is exacerbated throughout dialysis vintage, therefore compromising their quality of life. Despite recent studies highlighting improvements in physical function regardless of exercise modality, well-designed randomized controlled trials with progressive resistance exercise training protocols are scarce. Thus, this study investigated the effects of 12 weeks of intradialytic progressive resistance exercise (RE) and aerobic exercise (AE) training on physical function in HD patients. METHOD: Fifty-six adult HD patients from three NephroCare Portugal SA clinics were included in this study. Following a 6-week run-in control period, participants were randomly allocated into either a supervised intradialytic AE [( n = 29, male: 66%, age: 66 ± 16 years)] or RE [( n = 27, male: 67%, age: 63 ± 14 years)] training protocol, 3 sessions per week for 12 weeks. Intradialytic RE training consisted of 2 sets of 12 repetitions of 8 different exercises for upper and lower body using free-weight dumbbells and a newly designed weight machine, while intradialytic AE training was performed on a cycle ergometer at 50–70 rpm for 30 min at a rating of perceived exertion (RPE) 12–14 (Borg scale). Physical function was assessed by completing the Sit to Stand 60 (STS-60) test, the Short Physical Performance Battery (SPPB), the Incremental Shuttle Walk Test (ISWT), the Timed Up and Go (TUG) test and isometric handgrip strength (HGS) on three occasions: before and after the 6-week run-in control, and after the 12-week exercise periods. The 6-week control period data were analyzed by paired sample t -tests or Wilcoxon rank test as this is prior to randomization. Training effects were examined using an ANOVA with mixed design (within- and between-subjects) for data with normal distribution or if data still with non-normal distribution after log transformation, Wilcoxon rank test (within subjects) and Mann–Whitney test (between subjects) were used with a significance value of P < 0.05. RESULTS: There was no change in any variable when comparing before and after the 6-week control period (P > 0.05). AE and RE training significantly increased the number of repetitions performed on the STS-60 test compared to before the 12-week intervention, but had no effect on the SPPB scores. Additionally, despite no changes in the distance covered in ISWT in the AE group, AE training reduced the TUG time and an increase in HGS was observed. On the other hand, patients that performed RE training increased their walking distance in ISWT. However, no change in HGS was observed. Yet, and despite not impactful, a 0.1 s significant increase in the median time performed on the TUG test was also observed. Nevertheless, no changes between groups were observed after the 12-week exercise intervention (Table 1 ). CONCLUSION: We conclude that 12 weeks of AE training seem to improve HGS, STS-60 and TUG test performance in HD patients, whereas progressive RE training only had an effect on the STS-60 and ISWT performance in these patients. This may suggest that HD patients can benefit from different exercise interventions which can improve their overall physical function. FUNDING: Portuguese Foundation of Science and Technology (SFRH/BD/138 940/2018 and UID/04 045/2020). ACKNOWLEDGEMENTS: We would like to acknowledge the support of NephroCare Portugal, the University of Maia staff, MSc students and all study participants for their collaboration.